Nurses’ perception of patient safety culture using the Hospital Survey on Patient Safety Culture tool and its association with nursing-patient outcomes: a systematic review in Iranian hospitals - Alireza Hajizadeh; Behrouz Amini Kordkandi; Sevda Sadeghpour; Milad Khodavandi; Jalal Saeidpour; Edris Kakemam (BMC Nursing)
Abstract Background Current systematic review aimed to summarize the evidence that investigated the relationship between nurses’ perception of patient safety culture (PSC), as measured by the Hospital Survey of Patient Safety Culture (HSOPSC), and nursing-sensitive patient outcomes within Iranian hospital contexts. Methods This systematic review adhered to the Joanna Briggs Institute guidelines and employed the PRISMA flow diagram to manage the literature screening process. A search of international and local databases, (PubMed, Scopus, Web of Science, Scientific Information Database, IranMedex, and Magiran) was carry out. The Critical Appraisal Skills Program (CASP) checklist was applied to assess the risk of bias within the included studies. A narrative synthesis approach was employed, consisting of three stages: Creating a preliminary synthesis, examining the internal and external relationships of studies, and specifying the overall strength of the synthesized findings. Results From an initial pool of 1636 identified studies, 12 of them met the inclusion criteria for this review. These studies encompassed a total of 6001 nurses participating, predominantly working in teaching hospitals. Five studies indicated that positive nurse perceptions of patient safety culture (PSC) were associated with the prevention of adverse events (odds ratio: 0.61 to 2.28). One study reported that there was a significant negative relationship between PSC and barriers to rerror reporting by hospital nurses (r = − 0.42). Significant inverse correlations were observed between overall PSC score and missed nursing care (r = − 0.22), stress level (r = − 0.39 to − 0.46), and medication error (r = − 0.28). Furthermore, PSC demonstrated a positive correlation with social intelligence (r = 0.76) and psychosocial workplace factors (r = 0.88). Finally, PSC among nurses was significantly associated with a reduction in second-victim experience (β = − 0.39) and burnout (β = − 0.24). Conclusion This review recommends that hospital managers prioritize enhancing nurses’ perceptions of PSC to improve both nurse and patient outcomes. This can be achieved through interventions such as fostering collaborative and transparent communication within healthcare teams, facilitating the sharing of experiences and lessons learned, incorporating staff feedback, providing external support, cultivating a non-punitive environment, and implementing staff training programs. Further research is warranted to identify and evaluate specific interventions that effectively improve PSC and associated outcomes.